Densidade de Enterococcus sp em águas recreacionais e areias de praias do município de São Vicente-SP, Brasil e sua relação com parâmetros abióticos - Pinto, Aline Bartelochi [UNESP]; Pereira, Cristina Rocha [UNESP]; De Oliveira, Ana Júlia Fernandes Cardoso [UNESP] (My University, 2012)
Coastal cities attract a large number of tourists for their beautiful landscape and recreational activities, increasing the municipalities' income source. Thus, a need is clear for the establishment of beach quality monitoring programs to ensure bathers health. Although there is an effective monitoring program for recreational waters in Brazil there are no programs to certify the quality of beach sands. In this sense, the aim of this work was to analyze the density of bacteria from the genus Enterococcus in both sand and water from two beaches from São Vicente, São Paulo (Brazil) and correlate these densities to abiotic parameters such as: temperature, salinity, particle size, organic matter and tides). Water and sand samples were collected during February 2006 on the beaches of Gonzaguinha e Ilha Porchat and bacterial densities were determined by membrane filter technique. Temperature and salinity were measured in situ with a thermometer and a refractometer while particle size and organic matter were determined according to methods described by Suguio and Dean. There were significant differences between densities found in water and sand (p=0.004), being approximately 20 times higher in Gonzaguinha's beach sands. Similar results were found for Ilha Porchat beach samples, being the densities found in sand 3 times greater than those found in water. Both beaches showed a negative correlation between bacterial densities and salinity and temperature, suggesting a deleterious effect of these parameters on the bacterial community. On the other hand, no correlation was found between organic matter and particle size and bacterial densities. This work demonstrates that there is a great necessity for monitoring beach sand since the evaluation of beach quality is an important part of integrated coastal management programs.
Density of Enterococcus sp in recreational waters and beach sand in São Vicente-SP, Brazil and its relationship to abiotic parameters
Keywords: Coasts; Pollution Indicators; Public Health; Sand